Economic analysis of drip irrigation for growing Cherry Tomato (S. lycopersicon var. Pimpinelifolium L.) - ., MANISHA; SINHA, JITENDRA; ., SHASHIKANT; JANGRE, NILIMA; SAHU, RADHIKA (Journal of Soil and Water Conservation, 2020)
The experiment was laid out at Faculty of Agricultural Engineering Indira Gandhi Krishi Vishwavidyalya, Raipur with 12 treatments i.e. four irrigation level (100, 80, 60% and control) and three types of mulches (BPM, PSM and WM) having three replications. Furrow irrigation with and without mulch was treated as control. The effect of black plastic mulch (BPM), paddy straw mulch (PSM) and without mulch (WM) with four level of irrigation (100% CWR, 80% CWR and 60% CWR) on soil temperature, moisture level, yield, quantify the economics through drip irrigation system of cherry tomato was studied. The soil moisture depletion at 12 and 20 cm depth of the soil was evaluated by using time domain reflectometer (TDR). The soil temperature was recorded at 7:30 AM and 2:00 PM under different mulches conditions. It is found that at 7:30 AM and 2.00 PM the average soil temperature under BPM was higher as compared to other at 5 cm and 10 cm depth. Similarly, maximum soil moisture and minimum soil depletion was found under BPM followed by PSM and WM at 12 and 20 cm soil depth. The higher yield, income and benefit cost was recorded under 80% CWR drip irrigation system with BPM. The water saved with 80% of CWR - BPM treatment can be used for cultivating an additional area of 0.25 ha.